Effect of Post-splenectomy Booster Vaccine Program on Vaccination Compliance in Trauma Patients. Issue 5 (May 2021) - Gonzalez, Robert A.; Robbins, Justin M.; Garwe, Tabitha; Stewart, Kenneth E.; Sarwar, Zoona; Cross, Alisa M.; Celii, Amanda M.; Albrecht, Roxie M.
Objective: In 2012, the Centers for Disease Control and Prevention (CDC) Advisory Council on Immunization Practice recommended an additional post-splenectomy booster vaccine at 8 weeks following the initial vaccine. The objective of this study was to evaluate our vaccination compliance rate and what sociodemographic factors were associated with noncompliance following this recommendation. Materials and Methods: A retrospective review of a performance improvement database of trauma patients eligible for post-splenectomy vaccination (PSV) at a level I trauma center was carried out between 2009 and 2018. Overall and institutional compliance with PSV was compared before and after the addition of booster vaccine recommendation. Factors associated with booster noncompliance were also identified. Results: A total of 257 patients were identified. PSV compliance rate in the pre-booster was 98.4%, while overall and institutional post-booster compliance rate were significantly lower at 66.9% ( P ≤ .001) and 50.0% ( P ≤ .001), respectively. Compared to booster institutional compliers, institutional noncompliers lived farther from the trauma center (48 vs. 86 miles, P = .02), and though not statistically significant, these patients were generally older (34.9 vs. 40.5, P = .05). Discussion: PSV booster compliance is low even with the current educational materials and recommendations. Additional approaches to improve compliance rates need to be implemented, such as sending letters to the patient and their primary care providers (PCPs), collaborating with rehab/long-term acute care centers, communicating with city and county health departments and city pharmacies, or mirroring other countries and creating a national database for asplenic patients to provide complete information.